2021
DOI: 10.1080/07399332.2021.1898613
|View full text |Cite
|
Sign up to set email alerts
|

Women’s experiences of cultural and traditional health beliefs about pregnancy and childbirth in Zambia: An ethnographic study

Abstract: Zambian women's pregnancy and childbirth are linked to a variety of cultural and traditional practices, activities and beliefs. These existential events affect the women's health and the newborn's care. In this study we used an interpretative ethnographic design. Individual deep interviews with eight Zambian women were carried out. The formation of family, pregnancy and childbirth are important for strengthening generational traditions and preserving culture. Having many children is especially important for Za… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 24 publications
(35 reference statements)
2
16
0
Order By: Relevance
“…The name cannot be given if the child cries or is ill. It is the responsibility of the healer to discuss with the ancestor regarding whose name the child will be given (Honkavuo 2021). This is in line with the practice of the people of Omuma division in Imo State, Nigeria, who believe in reincarnation.…”
Section: The Naming Ceremonymentioning
confidence: 69%
See 3 more Smart Citations
“…The name cannot be given if the child cries or is ill. It is the responsibility of the healer to discuss with the ancestor regarding whose name the child will be given (Honkavuo 2021). This is in line with the practice of the people of Omuma division in Imo State, Nigeria, who believe in reincarnation.…”
Section: The Naming Ceremonymentioning
confidence: 69%
“…As an act of eloquent expression, rituals are a means of transmitting cultural beliefs and values with dramatic effect and emotive force (Grillo 2012). Despite criticism regarding adherence to ritual practices and taboos, it has been shown that some of the pregnancy and birth rituals have purificatory effects, provide protection for the mother and child from evil powers, and are therefore beneficial for maternal and newborn health (Nwadiokwu et al 2016;Honkavuo 2021). Dietary proscription is among the precautionary measures observed by women to promote health and ensure a normal and safe birth (Elom 2019;Honkavuo 2021).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Cultural norms and gender roles shape women's perceptions, beliefs, and expectations about pregnancy ( 11 , 12 ). In many African cultures, particularly in Ethiopia, pregnancy is highly valued to be shared with a spouse or husband, and a pregnant woman who has experienced a partner breakup may be concerned about failing to meet this societal value, which, when combined with other socioeconomic adversities, can lead to psychological or emotional stress.…”
Section: Introductionmentioning
confidence: 99%